High resolution β — γ coincidence spectrometry at the UK CTBT Radionuclide Laboratory. (December 2020) - Goodwin, M.; Britton, R.; Davies, A.; Regan, P. H.; Bell, S.
Abstract: Detection of radioxenon is often considered the most probable indicator of an underground nuclear explosion. GBL15 is the UK's Comprehensive Nuclear-Test-Ban Treaty Certified Radionuclide Laboratory, operated at AWE Aldermaston and has a history of developing high fidelity coincidence detection systems for particulate radionuclides. The Laboratory also operates a SAUNA II system, using NaI(Tl) and plastic scintillator detectors to measure β – γ coincidences from the decay of the four radioxenon isotopes, namely 133 Xe, 135 Xe, 131m Xe & 133m Xe. Here the efforts to date in exploring new technologies for next generation laboratory-based β – γ coincidence spectrometry for radioxenon measurements are discussed. Results are presented from preliminary measurements using a PIPSBox detector with a high purity germanium γ detector and the output compared to that of lower resolution systems. This investigation will be used to scope future programmes on the technology used for the measurement of radioactive noble gas nuclides at GBL15.